Historie van Mejuffrouw Cornelia Wildschut, of De gevolgen der opvoeding - Wolff, Betje 1738-1804; Deken, Aagje 1741-1804 (The Hague van Cleef, 1793)
This novel is mainly set in Holland at the end of the eighteenth century. The rich, beautiful but spoiled girl Cornelia is bored. A trickster persuades her to run away from home, dishonors her and abandons her. The seducer, dying after a duel for the honor of yet another girl, repents; the father is consumed by guilt for not having allowed his daughter to be raised responsibly and morally; the seduced miss, formerly an idle mind, turns into a god-worshipping supplicant, unable to bear the burden of her conscience and her father's death, and just as quickly exchanges the temporary for the eternal.
Title-page of vol. 1 is missing
Keywords: 18th Century (1701-1800); Novel; Netherlands